Fractal branch-like fractal shell-and-tube heat exchangers: A CFD study of the shell side performance. Issue 1 (2019) - Foster, Niall; Sebastia-Saez, Daniel; Arellano-Garcia, Harvey
Abstract: Nature has provided some of the most ingenious and elegant solutions to complex problems over millions of years of refining through evolution. The adaptation of Nature´s solutions to engineering problems is a recent trend which has opened opportunities for improvement in many areas ranging from Architecture to Chemical Engineering. In particular, the use of fractal geometries on heat exchangers is a recent design trend. Recent investigations highlight the benefit of implementing fractal-based geometries on the tube side of shell and tube heat exchangers. A complete evaluation of such devices by assessing the performance of the shell side has not been undertaken, though. Here, we present a systematic numerical assessment of the shell side of a tree-like shaped heat exchanger. Key performance parameters, i.e. temperature change, pressure drop and coefficient of performance, are obtained and compared to those of a straight tube, in order to fully understand the potential of the application of fractal-based shapes to the design of heat exchangers.